Relationship Between Kings and Worldly Beings in Kalingatthupparani - K, Akila; D, Mahila Jeni (International Research Journal of Tamil, 2022)
Tamil literature is one of the best literatures that has made the world aware of the greatness of relationships. Bharani is a type of literature that sings in praise of the success of the battlefield. If a king protects the citizens from any suffering, is kind to the living beings of the world, and rules impartially and ethically, the relationship between the king and the living beings of the world will be strengthened. The relationship blossoms in the expression of love. The relationship between Sibi, the Chola king who gave himself for a pigeon, with the dove, the relationship between Manuneethi Chola and the cow for the sake which he killed his own son to give justice to a cow, the relationship between the king of Pañasapa and the people who gave his own blood to the thirsty people, the relationship between the Chola who released the Cheran imprisoned for the poet who sang and entertained him, the relationship between Chenganan and poet, the relationship between the poets and the first Kulothunga Chola who gave gifts to the musicians, the relationship between the king who gives life to the soldiers and the soldiers of the army who are grateful to the king are all examined in this article.